Graphs with Clusters Perturbed by Regular Graphs—Aα-Spectrum and Applications - Cardoso Domingos M.; Pastén Germain; Rojo Oscar (Discussiones Mathematicae Graph Theory, 2020)
Given a graph G, its adjacency matrix A(G) and its diagonal matrix of vertex degrees D(G), consider the matrix Aα (G) = αD(G) + (1 − α)A(G), where α ∈ [0, 1). The Aα -spectrum of G is the multiset of eigenvalues of Aα (G) and these eigenvalues are the α-eigenvalues of G. A cluster in G is a pair of vertex subsets (C, S), where C is a set of cardinality |C| ≥ 2 of pairwise co-neighbor vertices sharing the same set S of |S| neighbors. Assuming that G is connected and it has a cluster (C, S), G(H) is obtained from G and an r-regular graph H of order |C| by identifying its vertices with the vertices in C, eigenvalues of Aα (G) and Aα (G(H)) are deduced and if Aα (H) is positive semidefinite, then the i-th eigenvalue of Aα (G(H)) is greater than or equal to i-th eigenvalue of Aα (G). These results are extended to graphs with several pairwise disjoint clusters (C1, S1), . . . , (Ck, Sk). As an application, the effect on the energy, α-Estrada index and α-index of a graph G with clusters when the edges of regular graphs are added to G are analyzed. Finally, the Aα-spectrum of the corona product G ◦ H of a connected graph G and a regular graph H is determined.